Level of services (Los) for public bus and passengers aspiration in Kerian district, Malaysia - Bachok, Syahriah; Mohamed Osman, Mariana; Ponrahono, Zakiah (AMER, 2018)
Public transportation facilitates the mobility of activities and goods from all sustainable development key dimensions. Over the past decades, more trips of public transportation move people towards a more sustainable future, by reducing congestion on the roads and increasing the efficiency of the road system. The research aims at analysing the passenger’s aspiration and perspective of sustainable public transport measure and evaluating Malaysian rural bus services, using the case study of Kerian District in the state of Perak. On-board intercept passenger survey and adoption of Geographical Information System (GIS) / Global Positioning System (GPS) were used to collect the primary data. The research suggested that whilst the services levels are less than those aspired by the passengers, there are many improvement areas to be prioritised in the near future. Keywords: Sustainable transportation; sustainable transport indicator; transport planning; sustainable transportation dimension; passenger’s aspiration. eISSN 2398-4279 © 2018. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia.